2022
DOI: 10.1097/j.jcrs.0000000000000950
|View full text |Cite
|
Sign up to set email alerts
|

Factors leading to realignment or exchange after implantable collamer lens implantation in 10 258 eyes

Abstract: ICL is a safe procedure with a low incidence of secondary surgery. Realignment, including vertical rotation, and exchange are practicable for the management of misalignment and excessive vault.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…In addition, the eyes of Asians and women are considered to have a genetic and anatomical tendency for angle closure [ 26 , 27 ]. Wei et al [ 28 ] found that 10 eyes (0.10%) underwent secondary surgery due to complications of excessive vault (range, 730–1190 μm) in 10,258 eyes that underwent ICL V4c implantation surgery for an average of 20 months. Hu et al [ 29 ] also reported a case of high intraocular pressure and secondary glaucoma due to angle narrowing (Shaffer II-III grade) after ICL implantation, and the postoperative vault was only 456 μm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the eyes of Asians and women are considered to have a genetic and anatomical tendency for angle closure [ 26 , 27 ]. Wei et al [ 28 ] found that 10 eyes (0.10%) underwent secondary surgery due to complications of excessive vault (range, 730–1190 μm) in 10,258 eyes that underwent ICL V4c implantation surgery for an average of 20 months. Hu et al [ 29 ] also reported a case of high intraocular pressure and secondary glaucoma due to angle narrowing (Shaffer II-III grade) after ICL implantation, and the postoperative vault was only 456 μm.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the decrease in arch height over time [ 83 ], in order to maintain sufficient arch height for a long time (> 10 years), the immediate arch height after operation should be greater than 550 µm [ 84 ], and for arch height below 150 µm, immediate removal and/or replacement with a more appropriate ICL should be considered [ 85 ]. Additionally, vertical rotation of an ICL may be a less invasive method to treat high arch height in certain cases [ 86 ].…”
Section: Summary and Treatment Of Postoperative Complications Of Iclmentioning
confidence: 99%
“…For patients with ICL implantation, spontaneous rotation only affected the arch height of patients to a certain extent, and for patients with TICL, it resulted in a significant loss of visual acuity [ 93 , 94 ]. The incidence of spontaneous rotation of TICL was about 0.12% [ 86 ]. Majid Moshirfar et al 's study showed that 87% of patients rotated < 5° after TICL implantation and did not require additional intervention [ 6 ].…”
Section: Summary and Treatment Of Postoperative Complications Of Iclmentioning
confidence: 99%
“…Since the TICL size recommended by the manufacturer does not consider the vertical position, we performed an additional comparison excluding the TICLs implanted with a vertical orientation (Fig. 1b) [18,19].…”
Section: Recommended Ticl Sizementioning
confidence: 99%